C COVID-19 Surveillance At Cempaka Public Helath Center (INTEGRATION PROCEEDING, 2023)
At the end of 2019, a pneumonia outbreak was found with no known exact cause. This outbreak was first detected in the city of Wuhan in Hubei Province of China. On January 7, 2020, researchers succeeded in identifying the cause of pneumonia, namely a type of novel coronavirus. The purpose of this study was to determine the incidence of Covid-19 cases by region, sex and age. The method used in this study is a descriptive method through a quantitative approach with secondary data types, namely data recapitulation that is available at the Cempaka Besar Health Center in 2021. The Cempaka Health Center work area has 4 sub-districts, namely Kelayan Luar, Mawar, Kertak Baru Ulu, and Kertak Baru Ilir. The number of Covid-19 incidents in the Cempaka Health Center work area reached 395 cases in 2021. Mawar Village reached 217, Outer Services 26 cases, Kertak Baru Ulu 54 cases, and Kertak Baru Ilir 97. In the Cempaka Health Center work area, namely 183 men and 395 women who were exposed to Covid-19 cases. The most cases of Covid were aged 26-50 years and totaled 165 cases while the lowest cases of Covid were aged 1-11 years amounted to 13 cases. cases for a total of 395 cases. data for overall cases 1-11 years 13 cases, 11-25 years 91 cases, 26-50 years 165 cases, 50-64 years 81 cases, 65> years 45 cases. The highest incidence of Covid 19 in the Mawar Village area is female, and in the 26-50 year age group.